Intravenous esketamine leads to an increase in impulsive and suicidal behaviour in a patient with recurrent major depression and borderline personality disorder. (21st October 2022) - Vanicek, Thomas; Unterholzner, Jakob; Lanzenberger, Rupert; Naderi-Heiden, Angela; Kasper, Siegfried; Praschak-Rieder, Nicole
Abstract: Objectives: As clinical studies demonstrated that ketamine possesses rapid-acting antidepressant and antisuicidal effects, it is increasingly used in affective disorders. The neuroplastic properties of ketamine are well described in preclinical and imaging studies, and are highly related to its antidepressive mechanism of action. Methods: Here, we report on a female patient with recurrent major depression and borderline personality disorder (BPD) who was treated with intravenous (i.v.) esketamine as rapid-acting augmentation therapy to improve severe and acute depressive symptoms and suicidal behaviour. Results: Esketamine led to an initial improvement of these symptoms. However, during the course of treatment, loosened and disinhibited behaviour and severe suicidal ideation occurred during and immediately after esketamine application. Hence, i.v. esketamine was discontinued, and she further received treatment as usual, which demonstrated to be beneficial. Conclusions: With current knowledge at hand, one cannot exclude esketamine's effects on the equilibrium of neural plasticity in brain networks, potentially initiating undesirable symptoms as impulsive behaviour and emotional dysregulation. Therefore, until investigations focus on efficacy and side effects profile of esketamine in depressed patients with (comorbid) BPD, treatment with this fast-acting medication should be considered with caution in this patient group.